Forgotten Deficiency: A Case Series Highlighting Atypical Presentations of Scurvy in the 21st Century - Mohammed Ayyad; Lilian Tran; Safia Ansari; Dennis Levy; Daniel Matassa (Case Reports in Medicine, 2025)
Scurvy, caused by vitamin C deficiency, is increasingly recognized in contemporary clinical practice, particularly among vulnerable populations. Despite its historical association with maritime exploration, scurvy persists in patients with malnutrition, alcoholism, psychiatric disorders, and limited access to fresh produce. This report presents two cases of scurvy diagnosed in a low socioeconomic urban setting, emphasizing the diverse and atypical manifestations of this condition. The first case involves a 76-year-old female presenting with altered mental status and pulmonary hypertension, ultimately attributed to severe vitamin C deficiency. Echocardiography revealed a pulmonary artery pressure of 36 mmHg and severe tricuspid regurgitation. A thorough evaluation, combined with evidence of malnourishment and neuropsychiatric symptoms, led to the diagnosis of scurvy, confirmed by undetectable serum vitamin C levels. High-dose intravenous vitamin C supplementation resulted in marked clinical improvement and resolution of cardiopulmonary abnormalities. The second case describes a 68-year-old male with alcohol use disorder presenting with syncope, anemia, and systemic inflammation. Laboratory tests revealed leukocytosis, acute kidney injury, elevated ferritin, and undetectable iron-binding capacity. A nutritional workup identified severe vitamin C deficiency (0.2 mg/dL). Oral vitamin C supplementation improved inflammatory markers, anemia, and general well-being. These cases highlight the importance of considering scurvy in patients with unexplained systemic symptoms and malnutrition. Early diagnosis and prompt treatment with vitamin C supplementation can lead to full recovery and prevent severe complications. Clinicians should maintain a high index of suspicion for scurvy, especially in at-risk populations with atypical clinical presentations.